Política online: campanha eleitoral no facebook - LOPES, Lucivane (Universidade Federal do Pará, 2017)
The present research aims to analyze Brazil's 2012 Election Campaign, describing the construction of "social capital" in the online social network 'Facebook'. The main goal is to analyze the importance of this vehicle as a catalyst of social capital and how these are transformed into political capital, that is, votes. In Brazil, social networks have expanded on their degree of importance for electoral campaigns, as these networks may encourage political engagement. The visibility on the web has been turned into results in the ballot boxes and/or into political capital. For this work, Netnography was used as a qualitative methodology for assessment of the hypothesis that political participation is extended with the emergence of online social networks.